Immune-Related Erythema Nodosum Mimicking in Transit Melanoma Metastasis on [18F]-FDG PET/CT - Romain-David Seban; Camille Vermersch; Laurence Champion; Benjamin Bonsang; Anissa Roger; Jerome Ghidaglia (Diagnostics, 2021)
Early detection of immune-related adverse events (irAEs) with immune checkpoint inhibitors (ICIs) is crucial, particularly when these are likely to mimic tumor progression, as well as sarcoid-like reactions. Here, we report the case of a 68-year woman, with a history of four primary cutaneous melanomas (thickest lesion with BRAF mutation removed from the left axilla 2 years before), who was diagnosed with BRAF V600E-mutant metastatic melanoma and treated by ICI targeting the PD-1 receptor. Follow-up whole-body positron emission tomography/computed tomography (PET/CT) using 18F-fluorodeoxyglucose ([18F]-FDG) was performed at 15 months, and FDG-avid subcutaneous nodules on her legs were detected. A biopsy from a lesion on her right leg was obtained, and histology strongly suggested erythema nodosum. Given the isolated nature of these lesions, the normal serum Angiotensin-Converting Enzyme and the context of ICI, an immune-related sarcoid-like reaction was retained as the most likely diagnosis. Recent literature in immune-oncology suggests that erythema nodosum could be directly related to ICI(s). Although erythema nodosum is a rare occurrence with imaging features overlapping with malignancy, it should be considered in the differential diagnosis of suspicious in-transit metastasis, especially when the patient is treated with ICIs and when lesions follow a bilateral distribution. In conclusion, nuclear medicine physicians should keep in mind this irAE when interpreting PET/CT scans in clinical practice in order to avoid false-positive findings.